Intraspecific variation and plasticity in mitochondrial oxygen binding affinity as a response to environmental temperature. Issue 1 (December 2017) - Chung, Dillon; Morrison, P.; Bryant, H.; Jung, E.; Brauner, C.; Schulte, P.
Abstract Mitochondrial function has been suggested to underlie constraints on whole-organism aerobic performance and associated hypoxia and thermal tolerance limits, but most studies have focused on measures of maximum mitochondrial capacity. Here we investigated whether variation in mitochondrial oxygen kinetics could contribute to local adaptation and plasticity in response to temperature using two subspecies of the Atlantic killifish (Fundulus heteroclitus ) acclimated to a range of temperatures (5, 15, and 33 °C). The southern subspecies ofF. heteroclitus, which has superior thermal and hypoxia tolerances compared to the northern subspecies, exhibited lower mitochondrial O2 P50 (higher O2 affinity). Acclimation to thermal extremes (5 or 33 °C) altered mitochondrial O2 P50 in both subspecies consistent with the effects of thermal acclimation on whole-organism thermal tolerance limits. We also examined differences between subspecies and thermal acclimation effects on whole-blood Hb O2 -P50 to assess whether variation in oxygen delivery is involved in these responses. In contrast to the clear differences between subspecies in mitochondrial O2 -P50 there were no differences in whole-blood Hb-O2 P50 between subspecies. Taken together these findings support a general role for mitochondrial oxygen kinetics in differentiating whole-organism aerobic performance and thus in influencing species responses to environmental change.